2021
DOI: 10.3390/vaccines10010010
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences in Knowledge and Attitude towards HPV and HPV Vaccine among College Students in Wenzhou, China

Abstract: Objective: This study aimed to determine human papillomavirus (HPV)-related awareness and willingness to receive HPV vaccination among college students, in Wenzhou, and its associated factors. Methods: A cross-sectional epidemiological study was conducted among college students in Wenzhou to investigate their knowledge, attitude, and factors affecting their willingness to receive HPV vaccination. Results: A total of 1035 questionnaires were collected, of which 1002 were valid (males: 374, females: 628). In tot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
20
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 39 publications
5
20
2
Order By: Relevance
“…The better results seen for female students in the present work agree with previously reported studies [49][50][51]. It may be that women show greater solidarity [52], or that since male students of nursing are reduced in number, they may more often decline to take part in group activities that might influence their attitudes [53].…”
Section: Discussionsupporting
confidence: 90%
“…The better results seen for female students in the present work agree with previously reported studies [49][50][51]. It may be that women show greater solidarity [52], or that since male students of nursing are reduced in number, they may more often decline to take part in group activities that might influence their attitudes [53].…”
Section: Discussionsupporting
confidence: 90%
“…A local study reported that men have a disproportionately low level of knowledge about HPV and its health association compared to women. 29 Similarly, in the present study, the median knowledge score of 5 out of a possible 15 implies a remarkably low level of knowledge about HPV and HPV vaccination among men, hence this warrants serious attention. The present study also identifies specific knowledge deficits that should be the target of awareness-raising education programmes for men in China.…”
Section: Discussionmentioning
confidence: 41%
“…In Romania, women are most likely willing to be HPV vaccinated; as revealed in our study, 126 (11.22%) women vs. 6 men (0.53%), ( p < 0.001) are HPV vaccinated, and the trend is the same in international studies; for example, in a similar study of 1035 responders in China, a total of 55.9% of males and 80.4% of females indicated that they would be willing to receive the HPV vaccine, a significant difference ( p < 0.001) [ 29 ], but the percentages differ drastically.…”
Section: Discussionmentioning
confidence: 91%